Primary gastric choriocarcinoma: A rare case. (2015) - Martins, Vilma Florença; Moreno, Filipa; Vizcaíno, J. Ramón; Santos, Jorge
Highlights: Primary gastric choriocarcinoma is a rare and aggressive tumour with poor prognosis. It is a β-HCG-producing tumour of trophoblastic cells. Most (70%) primary gastric choriocarcinomas have an adenocarcinoma component. Definitive diagnosis is usually made after surgery. The optimal treatment has not yet been established due to very few reported cases. Abstract: Introduction: Primary gastric choriocarcinoma accounts for 0.08% of all gastric cancers. It is a rapidly growing, widely metastatic and β-HCG-producing tumour of trophoblastic cells. Presentation of case: A 69-year-old white man presented to the hospital with symptomatic anaemia. An upper gastrointestinal endoscopy showed an ulcer of the cardia and lesser curvature, whose biopsy specimens proved to be malignant (carcinoma cells, non-specified). The patient underwent total gastrectomy with D2 lymphadenectomy. A histologic evaluation revealed a choriocarcinoma admixed with adenocarcinoma cells without lymph node metastases. The patient died from haemorrhagic shock, due to rupture of liver metastases and a massive haemoperitoneum, within 2 months of the initial presentation. Discussion: Primary gastric choriocarcinoma characteristics resemble those of gastric primary adenocarcinoma. The dedifferentiation theory is the most widely accepted theory to explain the pathogenesis of PGC. It is essential to rule out other possible primary lesions such as testicular tumour. The optimal treatment is not yet well established due to very few reported cases. Conclusion: Primary gastric choriocarcinoma is a rare tumour with an aggressive behaviour and very poor prognosis.